Quality factors influencing user satisfaction of mobile communication services in Kuwait - Alzabi, Tami H.M (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2016)
There is an enormous competition among major telecommunication service providers in Kuwait. Competition among service providers in limited population of Kuwait is a matter of survival of those companies to retain their customer base and remain in telecom business. Not only this, but to sustain competitive edge over each other. Kuwait's population is 4 M and the number of service subscriptions is 6.269 M. This means that an average user has 1.5 subscriptions. Currently, all three service providers have online services that provide instant services to their customers, such as paying bills, and checking details, news promotions, downloading media, and access to social networks. Telecom service providers are in state of chaos due to challenging environment and competition to manage customer base. Therefore, the purpose of this study is to investigate and identify service quality factors that can help these telecom companies to satisfy customer base and remain in business with competitive edge. In this research, an empirical study is carried out using a model consisting of three aspects: information quality, system quality, and service quality to measure mobile services' user satisfaction. In this regard, data was collected from the telecom users working in different service sectors in Kuwait. Data was analyzed using Statistical Package for Social Sciences (SPSS) and Analysis Moment of Structures Software (AMOS).The findings show that information quality, system quality, and service quality are three major constructs for user satisfaction. Therefore, this study suggest that mobile communication online service providers, in order to keep strong foothold in the market, must maintain information quality, service quality and system quality as top priority services for clients. This will help them gain more customers and win their loyalty, to compete in the market place, and maintain significant segments of the population as their potential customers in order to make good profit margin over others.